Recognition Distance and Elongation Ratio for Elongated Horizontal Pavement Markings: A Simulator Study - Scopoline, Kevin (My University, 2014)
All factors being equal, pavement marking signs are more likely to be detected by drivers than post-mounted signs. Several international manuals/guidelines explicitly state that elongation improves the legibility distance of pavement markings. Furthermore, some countries use greater elongation ratios on roadways with higher speed limits, while some others use a single elongation ratio regardless of the speed limit of the roadway. Therefore, research is needed to explore the relationship between speed and elongation ratio. Most of the available research on this topic has used stationary observers rather than subjects driving at posted roadway speeds, which makes a full-scale driving simulator an invaluable tool to study the effects of sign elongation on recognition distance while driving. Sixteen drivers, between the ages of 21 and 54, participated in the driving simulator study. Five elongation ratios that were tested in the driving simulator, 1:1, 1:2.5, 1:5, 1:7.5 and 1:10. The ?Curve? (W1-2) sign, ?Speed Limit? (R2-1) sign, and ?Pedestrian Crossing? (W11-2) sign were chosen for this research. Statistical analysis was performed to analyze the effect of elongation ratio on recognition distance through a random effects linear model. All variables were initially included and through the procedure it was found that age, gender, years of driving experience, and if the participant wore corrective lenses were not statistically significant covariates. It was found that elongation ratio, sign type, and speed were statistically significant factors when perception response time is not taken into account. The relationship between recognition distance and elongation ratio was found to be a quadratic function. While sign type is statistically significant, it is not meaningful for real world applications, therefore, the model was adjusted to be useful for all sign types. This research yielded a relationship between recognition distance and elongation ratio for drivers in a driving simulator: The constant term is affected by speed and whether a perception reaction time is used. Other considerations, such as cost of installation and maintenance, should be taken into account before an elongation ratio is selected for application.